A special event as a tool to implement PR-technologies in the library - A. Yu. Sergeeva; N. A. Turanina (Библиосфера)
Currently public relations are an integral part of management and a vital technology of our modern society. Especially the fact is undoubted that any organization activity nowadays is closely connected with the surrounding society and development of various kinds of contacts, libraries are no exception. Therefore, as a socio-cultural institution a library can’t ignore the effect of public relations on its activities. In addition, the time requires developing new mechanisms of libraries work, among them organizing a specific event is a PR perspective direction and tool. In market conditions this tool plays a significant role in improving the library image, and becomes an integral part of library work. In this regard, the study goal is to reveal the specificity of organizing a special event as a tool of public relations. The study objectives are the following: to reveal the essence of public relations and basic tools, to consider the problem of organizing of public relations in references, to justify the necessity of using special events as a tool of public relations, to describe the features of organizing special events, to develop a program of special events, namely opening the club «Literary Universe». The authors describe the stages of organizing special events in detail and offer various options to fill their contents. They have elaborated a special event program: opening the club «Literary Universe». The club aims to attract the youth to a library establishment and to make familiar this age group with the best works of Russian and foreign literature. The club opening ceremony consists of several stages: assessing the existing situation, setting goals and objectives, defining the target groups, time and place, estimating a budget, a scenario preparation, information support, evaluating the event effectiveness. Detailed characteristics of the above stages are presented in the article.